Amount of cholesterol in intercellular lipid models inversely correlates with hexagonal structure ratio in packing structures. (21st September 2022) - Terayama, Suzuko; Goto, Yutaka; Fukami, Toshiro
Graphical abstract: Highlights: Packing structure (PS) of intercellular lipids in skin is an important biological barrier. Examined effect of lipid decrease in the lipid model on the PS. PS assessed using DSC, Raman spectroscopy, and PXRD. Cholesterol inversely correlated with hexagonal structure ratio (RHex/Ort ) in the PS. RHex/Ort values highly correlated with amount of lipids eluted by surfactants. Abstract: The packing structure of intercellular lipids in skin forms an important biological barrier but little is known about the changes in packing structure caused by surfactant-induced lipid effluence. In this study, to examine the effect of the decrease in lipids in the lipid model (LM) on the packing structure, a single component was reduced from stratum corneum intercellular LM comprising ceramide ADS, cholesterol, and palmitic acid. The packing structure was assessed using differential scanning calorimetry, Raman spectroscopy, and powder X-ray diffraction. Surfactants were applied to LM to investigate lipid elution and changes in the packing structure. The results showed that the decrease in cholesterol caused disorder in the lipid structure and the amount of cholesterol was strongly inversely correlated with the hexagonal structure ratio (RHex/Ort ) in the packing structure. Furthermore, the RHex/Ort values were highly correlated with the amount of lipids eluted by surfactants, making it possible to measure lipid elution using RHex/Ort values. The methods used in this study are a useful alternative to native intercellular lipids for elucidating mechanisms underlying skin irritation due to surfactants.